2004
DOI: 10.1037/0022-006x.72.5.885
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Approach to the Assessment of Self-Mutilative Behavior.

Abstract: This study applied a functional approach to the assessment of self-mutilative behavior (SMB) among adolescent psychiatric inpatients. On the basis of past conceptualizations of different forms of self-injurious behavior, the authors hypothesized that SMB is performed because of the automatically reinforcing (i.e., reinforced by oneself; e.g., emotion regulation) and/or socially reinforcing (i.e., reinforced by others; e.g., attention, avoidance-escape) properties associated with such behaviors. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

109
1,271
9
49

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 1,179 publications
(1,438 citation statements)
references
References 19 publications
109
1,271
9
49
Order By: Relevance
“…The FASM includes 22 reasons for which a person may engage in NSSI, and the participant endorses each on a 0-3 scale. Confirmatory factor analysis and reliability analyses have demonstrated that these 22 items represent four over-arching functions of NSSI including automatic negative reinforcement, automatic positive reinforcement, social negative reinforcement, and social positive reinforcement (Nock & Prinstein, 2004), and subsequent work has supported the construct validity of these four functions (Nock & Prinstein, 2005).…”
Section: Non-suicidal Self-injurymentioning
confidence: 92%
See 2 more Smart Citations
“…The FASM includes 22 reasons for which a person may engage in NSSI, and the participant endorses each on a 0-3 scale. Confirmatory factor analysis and reliability analyses have demonstrated that these 22 items represent four over-arching functions of NSSI including automatic negative reinforcement, automatic positive reinforcement, social negative reinforcement, and social positive reinforcement (Nock & Prinstein, 2004), and subsequent work has supported the construct validity of these four functions (Nock & Prinstein, 2005).…”
Section: Non-suicidal Self-injurymentioning
confidence: 92%
“…Data suggest that approximately 4% of adults in the US population exhibit NSSI (Briere & Gil, 1998;Klonsky, Oltmanns, & Turkheimer, 2003), and that adolescents are at even higher risk, with approximately 12-21% reporting a lifetime history of NSSI (Ross & Heath, 2002;Whitlock, Eckenrode, & Silverman, 2006;Zoroglu et al, 2003). Recent research has begun to systematically describe the form and function of NSSI (Brown, Comtois, & Linehan, 2002;Nock & Prinstein, 2004, 2005; however, the potential pathways to this behavior are not well understood. One consistently reported relation is that between a history of child maltreatment, defined here as ARTICLE IN PRESS www.elsevier.com/locate/brat 0005-7967/$ -see front matter r 2007 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some instances people use physical behavior to harm themselves, which is often much more difficult to understand. In this paper, I further elaborate on our theoretical model on the social functions of self-injurious behaviors (Nock & Prinstein, 2004) by describing how and why people may escalate to the use of self-injurious behaviors as a means of influencing the behavior of others when less intense forms of communication fail. This rarely occurs at a societal level in an attempt to resolve cross-national conflicts or establish social order (except perhaps in instances of hunger strikes or self-sacrifice) (e.g., Brockman, 1999;Durkheim, 1897;Goldney & Schioldann, 2004), but more often happens on an individual level in an attempt to provide a signal of distress intended to elicit caregiving behavior in others, to provide a signal of strength intended to ward off potential aggressors, and in some cases to increase affiliation with others in a valued social group.…”
mentioning
confidence: 99%
“…Given the frequency of suicidal behavior among those suffering from BPD, many of the patients whom she studied met criteria for the diagnosis. More recent leading research focuses on suicidal and self-injurious behaviors across diagnoses [75] and is not limited to "focal" areas within BPD groups, but rather studying the construct across patient groups. Such approaches illustrate the benefit of targeting components of the diagnosis that are more broadly cut across other disorders, addressing to a certain extent the problems of comorbidity, but also by not unduly restricting variance by limiting it to a particular diagnosis.…”
Section: Conclusion and New Directionsmentioning
confidence: 99%